3(2x-5)-4=33

Simple and best practice solution for 3(2x-5)-4=33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-5)-4=33 equation:


Simplifying
3(2x + -5) + -4 = 33

Reorder the terms:
3(-5 + 2x) + -4 = 33
(-5 * 3 + 2x * 3) + -4 = 33
(-15 + 6x) + -4 = 33

Reorder the terms:
-15 + -4 + 6x = 33

Combine like terms: -15 + -4 = -19
-19 + 6x = 33

Solving
-19 + 6x = 33

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '19' to each side of the equation.
-19 + 19 + 6x = 33 + 19

Combine like terms: -19 + 19 = 0
0 + 6x = 33 + 19
6x = 33 + 19

Combine like terms: 33 + 19 = 52
6x = 52

Divide each side by '6'.
x = 8.666666667

Simplifying
x = 8.666666667

See similar equations:

| log(3x-4)=-0.1 | | 2xy+y=7 | | 5(2x+2)=9x+3 | | 6.3=2x-(-4.5) | | 4(2x-5)=-2(1-x) | | 9XY^2-6Y^3=0 | | 3b^2+3=0 | | 100-4d=40 | | 700+0.2x=1800 | | -3+15=4b-8-3b | | Y=1.14x+6 | | P=20+.05Q | | X(15+1)=6 | | Y=4(0.95)t | | f(x)=10+4x | | 5t*t-7t-60=0 | | ln(4-x)=20 | | 2.9=7.1-0.7x | | 11m^2-10m+2=9 | | 7p-3r+8p-2r= | | (a-1)(a+2)=0 | | 5x-18=3x-21 | | 10x+7=15x-6 | | 2x-6=7x-36 | | 2.12=1.2+0.32 | | 16x^4-81x^2+1=0 | | 5m*4m=72 | | (4x)+80=180 | | 3q-(-7q)= | | y+4=y-2 | | M^2+144=0 | | 3x-6=4x-14 |

Equations solver categories